Halitosis and Its Psychosocial Consequences on Dental Students' Quality of Life - Suci Erawati; Molek Molek; Salsabila Razmi Harahap (Jurnal Kesehatan Gigi, 2026)
Halitosis is a significant oral health concern with considerable psychosocial consequences, particularly among dental students who are expected to uphold exemplary oral hygiene as future professionals. This study investigated the association between halitosis and quality of life among dental students at Universitas Prima Indonesia. A cross-sectional design was employed, involving 31 dental students selected through purposive sampling from August to September 2025. Halitosis was objectively assessed using the Tanita Breath Checker and categorized into three severity levels, whereas quality of life was evaluated using the validated Oral Health Impact Profile-14 (OHIP-14) questionnaire. The findings indicated that 51.6% of participants experienced moderate halitosis, while 58.1% reported moderate impairment in quality of life. Statistical analysis revealed a significant correlation between halitosis severity and quality of life (p = 0.001), demonstrating a clear gradient relationship in which greater halitosis severity corresponded to poorer quality of life. Notably, all respondents reported inadequate tongue-cleaning and mouthwash use despite their dental training. These findings underscore a critical paradox in dental education: future oral health professionals exhibiting suboptimal oral hygiene practices that contribute to halitosis and, in turn, negatively affect their well-being. The study highlights the need to integrate targeted oral health promotion initiatives into dental curricula to address both the clinical and psychosocial dimensions of halitosis, thereby enhancing the professional competence and overall well-being of dental students.